(3OjhGf YeGQI Gdjefis - (3YeGQI Gdjefj , YeGQI Hf Ydj Hf RjOGf GdMcej GdePMLj Gdjefj, fLe GdOjf CHh eMeO,J (B569 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA bGajI GdgeRI Hbhdg hGdHQb jTgO hGdQhGYO CfgG YfhGf cd SMGHI hWaGA s
(3BNQgG (B:s
(3ef bGajI GdjGA (B: (3QVjJ HGdcJH HYO GdbQH hGfbWYJ MJi QVjJ SdGeG ai MhGTgjG s
(3HBNQg YOI ebWhYGJ dHYV GdTYQGA hde jSges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B193s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG CQVg s
Keywords: (3GdCOHs